Construction: Innovative Approach to Cost Accounting - Nikolaevna Gerasimova, Larisa; ., . (International Journal of Engineering and Technology, 2018)
Based on the study of existing methods of cost accounting, this paper examines the innovative approach to the calculation of products.The article shows that at the time of the decision on investing in a business project related to the development and construction of a new facility, it is advisable to use the target-costing methodology to forecast the cost of a product. For this purpose, when calculating the cost of a product, it is necessary to consider the market research indicators and the values of cost drivers.The author gives an example of using the â€œtarget-costingâ€ method in a construction organization, considering peculiarities of this method in construction.Based on the results of the study, it can be concluded that the proposed method of cost calculation for a future innovative product allows for an adequate assessment of future costs, which, given a shortage of raw data and the time resource, reduces investment risks.Â Â